The sloped limiting current region during ion transfer at arrays of nanointerfaces between immiscible electrolyte solutions - Rimboud, Mickaël; Austen, Benjamin J.J.; Strutwolf, Jörg; Liu, Yang; Arrigan, Damien (2024)
The formation of arrays of nano-interfaces between immiscible electrolyte solutions using nanoporous membranes opens up new opportunities in electrochemical analysis. However, an unusual feature in the voltammetry, in the form of a consistently sloped current in the limiting current region, has been observed. This sloped limiting current was observed using different alkylammonium cation transfers at the nanoITIES arrays, showing the generality of the feature. Experiments with variable concentrations of organic or aqueous phase electrolytes revealed that the sloped limiting current was impacted by the concentration of the aqueous phase electrolyte. A plausible explanation for the effect is discussed based on ternary electrodiffusion which occurs due to facilitated ion transfer of the aqueous phase background electrolyte cation. As a result, the use of nanoITIES arrays as the basis for chemical sensors and detection needs to be carefully considered.